Blood flow perfusion in visual pathway detected by arterial spin labeling magnetic resonance imaging for differential diagnosis of ocular ischemic syndrome - Chen, Yanan; Feng, Xue; Huang, Yingxiang; Zhao, Lu; Chen, Xi; Qin, Shuqi; Sun, Jiao; Jing, Jing; Zhang, Xiaolei; Wang, Yanling (Frontiers in Neuroscience, 2023)
Background：Ocular ischemic syndrome (OIS) attributable to chronic hypoperfusion caused by marked carotid stenosis is one of the important factors that cause ocular neurodegenerative diseases such as optic atrophy. The study aims to detect blood flow perfusion in visual pathway by arterial spin labeling (ASL) magnetic resonance imaging (MRI) for differential diagnosis of OIS. Methods：This diagnostic, cross-sectional study at a single institution was performed to detect blood flow perfusion in visual pathway based on 3D pseudocontinuous ASL (3D-pCASL) by 3.0T MRI. A total of 91 participants (91 eyes) consisting of 30 eyes with OIS, 61eyes with non carotid artery stenosis related retinal vascular diseases (39 eyes, diabetic retinopathy and 22 eyes, high myopic retinopathy) were consecutively included. Blood flow perfusion values in visual pathway derived from regions of interest of ASL images include retinal-choroidal complex, intraorbital segments of optic nerve, tractus opticus and visual center were obtained and compared with arm-retinal circulation time and retinal circulation time derived from fundus fluorescein angiography (FFA). Receiver operating characteristic (ROC) curves analyses and Intraclass correlation coefficient (ICC) were performed to evaluate the accuracy and the consistency. Results：Patients with OIS had the lowest blood flow perfusion values in the visual pathway (all p＜0.05). The relative intraorbital segments of optic nerve blood flow values at postlabeling delays (PLDs) of 1.5 seconds (area under curve, AUC=0.832) and the relative retinal–choroidal complex blood flow values at PLDs of 2.5 seconds (AUC=0.805), were effective for differential diagnosis of OIS. The ICC of the blood flow values derived from retinal–choroidal complex and intraorbital segments of optic nerve between the two observers showed satisfactory concordance ( all ICC＞0.932, p<0.001). The adverse reaction rates of ASL and FFA were 2.20% and 3.30%, respectively. Conclusion：3D-pCASL showed the participants with OIS had lower blood flow perfusion values in visual pathway, which presented with satisfactory accuracy，reproducibility and safety. It is non-invasive and comprehensive differential diagnostic tool to assess blood flow perfusion in visual pathway for differential diagnosis of OIS.